Advances in the Evaluation and Management of Children with Portal Hypertension - Ling, Simon C. (Seminars in Liver Disease, 2012)
Portal hypertension commonly accompanies advanced liver disease and gives rise to severe and life-threatening complications, including hemorrhage from esophageal varices. Diagnosis of portal hypertension in children currently relies on finding evidence of splenomegaly and the formation of portosystemic collaterals. There is a paucity of pediatric data to support the use of primary prophylaxis against variceal hemorrhage. A combination of vasoactive drug and endoscopic therapy should be used to manage variceal bleeding. Prevention of rebleeding is best achieved by endoscopic variceal ligation. Rex bypass surgery is the optimal therapy for prevention of further bleeding from portal vein thrombosis. Options to manage recurrent bleeding while on preventative therapy include surgical portosystemic shunt, Rex bypass, transjugular intrahepatic portosystemic shunt (TIPS), and liver transplantation. Management of gastric varices may require injection of cyanoacrylate glue or TIPS.
Keywords: portal hypertension; esophageal varices; gastric varices; variceal hemorrhage